2021
DOI: 10.21831/cp.v40i1.33755
|View full text |Cite
|
Sign up to set email alerts
|

Image-Text Relation Interpretation: Teachers’ Visual-Verbal Competence in Teaching Texts

Abstract: Multimodal literacy instruction is such a new shift of the literacy in which the construction of knowledge is led to be more socially and contextually bounded. Due to the urgency that teachers have to own multimodal competencies, this study aimed to investigate EFL teachers’ competence in interpreting visual-verbal relations to teach multimodal texts. To collect the data, an online test through the Google form platform was distributed. As many as 43 responses were collected from junior and senior high school t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover it can boost the students' perspectives using their opinions (Handayani et al, 2020). The video consists of various multimodal modes, such as movements, moving images, gestures, speech, and written language, which could encourage the students' thinking skills to convert and get a message (Fajriah et al, 2021). The written language contains the printed-linear text of the Child Gods story for the classifying task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover it can boost the students' perspectives using their opinions (Handayani et al, 2020). The video consists of various multimodal modes, such as movements, moving images, gestures, speech, and written language, which could encourage the students' thinking skills to convert and get a message (Fajriah et al, 2021). The written language contains the printed-linear text of the Child Gods story for the classifying task.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be concluded that all students could comprehend the narrative text using different modes and stories. Seeing this, a study has been conducted by Fajriah et al, (2021) that the teacher should consider and determine the modes (picture, video, written language, etc) to accomplish the aim of the text and the content for the students to comprehend the text easily in the teaching and learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the multimodal concept has commonly been studied in various ways in English Language Teaching (ELT). For instance, multimodality as learning models in EFL classes (Farías et al, 2011;Ilmi & Dewi, 2022), multimodality in literary work (Eisenmann & Summer, 2020;Thompson & McIlnay, 2019), multimodal texts analysis in academic discourses (Caple, 2018;Fajriah et al, 2021), multimodal literacy in language practice (Hafner, 2020;Serafini, 2015;Walsh, 2010), multimodal teaching in a writing class (Ryu & Boggs, 2016), multimodal communication in ELT (Hafner, 2020), the effect from multimodal tasks on students language abilities (Lim & Polio, 2020;Varaporn & Sitthitikul, 2019), and gender representation in the multimodal textbook (Ahour & Zaferani, 2016;Marefat & Marzban, 2014). However, as far as the researchers are concerned, no research has identified the pre-service teachers' perceptions of using multimodal texts in microteaching classes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first language learning materials are more often found to contain more text in their contents. If there is an image, usually its function is only as a decoration to beautify the appearance of the page, there is no more function [2]. Even though the images in the teaching materials can be used to evoke the discussion.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects added to teaching materials are not only useful for beautifying teaching materials, but have meaning and relevance in maximizing students' understanding of language learning. [2]. This article will discuss the development of teaching materials for the enrichment of Indonesian for Foreign Speakers or what is called BIPA.…”
Section: Introductionmentioning
confidence: 99%